Building Bridges: Fostering Collaborative Education in Training Dental Informaticians - Felix Gomez, Grace Gomez; Mao, Jason M.; Thyvalikakath, Thankam P.; Li, Shuning (Applied Clinical Informatics, 2025)
Background Dental informatics (DI) is an emerging discipline. Although the accreditation agency governing dental education programs asserts the importance of informatics as foundational knowledge, no well-defined DI courses currently exist within the standard predoctoral dental curriculum. There is a nationwide lack of DI academic programs. This training gap is due to a lack of qualified dental informaticians to impart knowledge on DI.Objective This paper aims to introduce a novel conceptual framework for an interdisciplinary DI program in preparing students to become dental informaticians.Methods In 2023, we developed a standalone graduate certificate program in DI at Indiana University (IU) School of Dentistry (IUSD) in collaboration with IU Luddy School of Informatics, Computing, and Engineering and IU Fairbanks School of Public Health. Feedback was collected through online surveys to assess course quality from students who took Introduction to Health Information in Dentistry. Feedback was analyzed qualitatively, utilizing a thematic analysis approach. Common responses relevant to DI education were grouped into themes.Results Five major themes emerged during our analysis of the students' feedback: foundational knowledge and skills; experiential learning: learning by doing; access to resources and working on clinical information systems; health promotion through team-based learning; and retention of knowledge assessment and application. A conceptual framework was formulated through these themes as a guideline for future program improvement. This interdisciplinary educational program framework showed how students and faculty from various disciplines could collaborate, learn from each other, and bring in expertise from different domains. The collaboration happens in clinical, laboratory, and virtual settings to acquire hands-on learning through practice and research projects.Conclusion The developed conceptual framework aligns with the interdisciplinary nature of DI. It can potentially be adopted by other interdisciplinary informatics programs in health and non-health care disciplines.
Keywords: dental informatics; experiential learning; interdisciplinary; accreditation standards; conceptual framework